Kearifan Lokal yang Responsif Moralitas Perempuan dalam Legenda Mata Likku di Sumba NTT - Kelen, Konradus Doni; Nusa, Silvester; Bitu, Yuliana Sesi; Bili, Mace (Paedagogie, 2026)
Culture is a dynamic construct that evolves alongside the changing needs of human life. This study seeks to foster cultural awareness among the Sumbanese people regarding the importance of recognizing and empowering women to define their own identities. The aim is to advocate for women's rights within the Sumbanese cultural framework, striving for a more just and egalitarian society. Employing a qualitative ethnographic approach, this research explores the role of local knowledge in shaping social behavior. The findings reveal that, at its core, Sumbanese culture holds deep respect for women, who are seen as moral agents with strong integrity. Moral intelligence, the capacity to distinguish right from wrong, significantly influences individuals’ commitment to integrity and their willingness to challenge cultural norms that marginalize women. The Legend of Mata Likku serves as a powerful expression of local wisdom that can be reinterpreted to catalyze cultural change and dismantle patriarchal systems in Sumbanese society